MIGRATION PROCESSES IN THE NATIONAL ECONOMY SYSTEM AND THEIR IMPACT ON THE STATE'S ECONOMIC SECURITY - HAVLOVSKA, N.; RUDNICHENKO, Ye.; RUDNICHENKO, M. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the peculiarities of the formation of migration processes and the main reasons for their occurrence. The pandemic has intensified migration processes that directly affect the state of economic security of national economies and the development of the national economy of any country as a whole. A significant number of migrant workers returned home during the pandemic, but the situation with the provision of able-bodied people did not improve. This has placed an additional burden on the country's social security system and created a number of threats to the country's economic security. The article examines the evolution of the essence of economic security and analyzes the terminological definition of the concept of "economic security of the state", as well as the main approaches to understanding this concept. It is established that due to the low interest of potential investors in opening new enterprises in the country and reducing production and, accordingly, employment opportunities, migration processes can have a rather negative impact on trends in socio-economic development. It is emphasized that the unambiguous assessment of migration processes on the state of the country's economy and economic security is unacceptable, because along with the loss of active population within the national economy, there is cash flow, which stimulates domestic consumption and increases purchasing power. The rating of Ukraine among the countries of the world according to the Global Peace Index during 2008-2020 is given, and it is determined that in 2020 according to the Global Peace Index Ukraine took the 148th place among 163 countries of the world. It is determined that minimizing the negative consequences of the military conflict in the east of the country is a priority area of foreign economic relations with European partners, and is a guarantee not only of economic but also national security.
Keywords: national security; economic security; migration; migration processes; pandemic; socio-economic development; military actions